Tinjauan Maqashid Syariah Terhadap Reklamasi Pesisir Pantai Jakarta - Masyhadi, Ahmad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
The reclamation of the Jakarta coast coast does have benefits, namely the opening of new jobs and the utilization of the area to be economically productive. With the presence of new jobs, unemployment will be reduced and at the same time people will get income to meet their daily needs and continue their lives. This is in line with the maqashid of sharia, namely hifzhu an-nafsi (guarding the soul). However, coastal reclamation also causes a lot of damage / damage, including environmental damage, silting of the seashore which causes water to flood residents when the rainy season arrives, and an increased risk of tsunami waves. Thus the safety and security of citizens is threatened. This is of course contrary to the maqashid of sharia, namely hifzhu an-nafsi (guarding the soul). In conditions like this we are faced with two choices, namely rejecting adversity or achieving benefit. So the best solution is to give priority to rejecting infidelity based on the rules of fiqh: